Penegakan Hukum dan Sanksi Serta Kendala pada Peraturan Daerah Kota Semarang Nomor 3 Tahun 2013 Tentang Kawasan Tanpa Rokok - Tiara Cantika Puja Ramadani; Dyah Listyarini; Arikha Saputra (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Smoking is the act of inhaling tobacco smoke, which has serious impacts on health and society. Even though reduction efforts have been made, Indonesia has a high smoking prevalence rate. No-Smoking Areas are regulated by Law Number 3 of 2013. Challenges in enforcing the rules arise in public places, with a lack of awareness and supervision. This research highlights the obstacles and effectiveness of law enforcement by Satpol PP in Semarang City regarding Regional Regulation Number 3 of 2013 concerning No-Smoking Areas. This research uses qualitative methods to explain the interactions between researchers and respondents. Research parameters include analysis and description. The data source is secondary data from primary and secondary legal materials. Data collection methods involve interviews, observation, literature study, and documentation. Data is presented in narrative form, and data analysis uses a qualitative normative approach. The research focuses on enforcing no-smoking area rules in the city of Semarang. Semarang, capital of Central Java, Indonesia. The research highlights the enforcement of Semarang City Regional Regulation Number 3 of 2013 concerning No-Smoking Areas. Routine Satpol PP outreach in schools, public places, offices and tourist attractions increases public awareness. Sanctions include warnings, statements that you will not smoke, and sanctions for minor crimes. The main obstacles involve societal ignorance and a lack of human resources. However, increased awareness since 2017 shows positive progress. This research concludes that the implementation of Semarang City Regional Regulation Number 3 of 2013 concerning No-Smoking Areas has succeeded in increasing public awareness through routine Satpol PP outreach. Sanctions are applied systematically and progressively, in accordance with regulations, with the potential to reduce tobacco consumption. The main obstacle involves community ignorance, requiring cooperation from the government, Satpol PP, Non-Governmental Organizations, and communities to increase understanding and compliance. Suggestions involve stronger synergies, comprehensive implementation methods, and active cooperation to achieve efficient and sustainable smoke-free areas in Semarang City.